Enzyme nomenclature 1992 : recommendations of the Nomenclature Committee of the International Union of Biochemistry and Molecular Biology on the nomenclature and classification of enzymes - Webb, Edwin C. (Edwin Clifford) (Published for the International Union of Biochemistry and Molecular Biology by Academic Press, 1992)
Recommendations of the Nomenclature Committee of the International Union of Biochemistry and Molecular Biology on the Nomenclature and Classification of Enzymes.